2020
DOI: 10.1093/socpro/spaa008
|View full text |Cite
|
Sign up to set email alerts
|

Complex Colorblindness in Police Processes and Practices

Abstract: Racial disparities in police-community encounters are well documented, with people of color experiencing higher levels of police scrutiny. Far less is known about how police officers perceive the racial dynamics at play in their work. As part of a 2016 study of traffic stops in San Diego, we conducted in-depth interviews with 52 city police officers. Despite evidence of racial disparities in SDPD practices related to post-stop outcomes, officers denied, minimized, or even condemned racial profiling during traf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…There is a general belief that discrimination is no longer an issue in prosecution, and most prosecutors are reluctant to consider whether they can play any further role in reducing racial disproportionality in criminal justice. These findings are consistent with prior work that highlighted the acceptance of colorblindness in criminal justice law and policy (Peery, 2011;Williams, 2019) and among other justice professionals such as police and corrections officers (Couloute, 2019;Welsh et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…There is a general belief that discrimination is no longer an issue in prosecution, and most prosecutors are reluctant to consider whether they can play any further role in reducing racial disproportionality in criminal justice. These findings are consistent with prior work that highlighted the acceptance of colorblindness in criminal justice law and policy (Peery, 2011;Williams, 2019) and among other justice professionals such as police and corrections officers (Couloute, 2019;Welsh et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In the context of policing, a recent study showed that experienced officers build their "own" expertise on locally specific profiles based on their experiences, which can lead to racially biased policing practices. At the same time, they claim to operate under a neutral policy of "color blindness" (Welsh et al, 2020). As pointed out previously, the greater the frequency of stopping people of color, the more likely they are to be fearful rather than feeling safe (Pickett et al, 2021).…”
Section: Expert Immunitymentioning
confidence: 91%
“…The rise of evidence-based policing as a method of making decisions about “what works in policing” (Sherman, 2013) advocates the use of technology, which, in turn, can introduce such biases. Although using scientific evidence unarguably has benefits, evidence-based practice per se is not immune to bias (Every-Palmer and Howick, 2014; Wieringa et al, 2018). In medicine, the very domain that informed evidence-based policing (Sherman, 1998), bias has been demonstrated in tested and proven hypotheses, study designs and selective publications (Every-Palmer and Howick, 2014).…”
Section: Fallacies About the Nature Of Biasesmentioning
confidence: 99%
“…These requirements are motivated by an effort to document officers' use of discretion in an area of policing widely believed to perpetuate racial inequality (e.g., Rojek et al, 2012;Smith & Petrocelli, 2001). To an officer who does not see driver race as affecting their own decision-making or the distribution of traffic stops more broadly (Welsh, Chanin, & Henry, 2020), data collection only redounds to their detriment. As one Boston Police Department union representative noted in response to the release of a report analyzing the racial distribution of traffic stops conducted across the state of Massachusetts, "Police officers, already second-guessed and harangued by the media, will respond [to the release of the report] by not enforcing traffic laws, out of a legitimate and real fear of being forced to participate in the manufacture of their own noose" (Dedman, 2004).…”
Section: Rule Compliancementioning
confidence: 99%